Bahasa Inggris: Bahasainggris - INAYATI, TITIK (Jurnal Ilmiah Ekonomi Islam, 2025)
BMT Usaha Gabungan Terpadu Sidogiri, as a sharia microfinance institution, has uniqueness and different characteristics because it has a background as an Islamic boarding school. This study aims to empirically determine: 1) How is the performance of the BMT Usaha Gabungan Terpadu from the perspective of maqashid sharia?, (2) What is the performance model of the BMT Usaha Gabungan Terpadu from the perspective of maqashid sharia? This study uses a qualitative method with an emphasis on what is expressed, understood, and felt through the statements and interpretations of informants. The results of this study indicate (1) The performance of BMT Usaha Gabungan Terpadu Sidogiri meets the perspective of maqashid sharia, namely the existence of family welfare felt by the community has met the five aspects of maqashid sharia, (2) The research model of the performance of BMT Usaha Gabungan Terpadu Sidogiri shows different characteristics from other sharia financial institutions. Performance from the perspective of maqashid sharia is not seen from its ability to generate profits, but the benefits felt by members and the surrounding community in improving their welfare.